2014
DOI: 10.1371/journal.pone.0086366
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Effects of the Diet on the Microbiome and the Local and Systemic Immune Response in Mice

Abstract: Outside the nutrition community the effects of diet on immune-mediated diseases and experimental outcomes have not been appreciated. Investigators that study immune-mediated diseases and/or the microbiome have overlooked the potential of diet to impact disease phenotype. We aimed to determine the effects of diet on the bacterial microbiota and immune-mediated diseases. Three different laboratory diets were fed to wild-type mice for 2 weeks and resulted in three distinct susceptibilities to dextran sodium sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…It was recently reported that feeding purified diets enhanced the susceptibility of mice to DSS-induced colitis; this effect was partially mediated by the gut microbiome and was associated with diet-mediated effects on the systemic immune response [47]. Our study demonstrated that the effect of the overall dietary fibre content on intestinal microbiota and cecal SCFA formation in HLA-B27 transgenic rats was greater than the effect of supplementation with IMO or FOS.…”
Section: Discussionsupporting
confidence: 50%
“…It was recently reported that feeding purified diets enhanced the susceptibility of mice to DSS-induced colitis; this effect was partially mediated by the gut microbiome and was associated with diet-mediated effects on the systemic immune response [47]. Our study demonstrated that the effect of the overall dietary fibre content on intestinal microbiota and cecal SCFA formation in HLA-B27 transgenic rats was greater than the effect of supplementation with IMO or FOS.…”
Section: Discussionsupporting
confidence: 50%
“…This is confirmed by studies in other disease models, such as immune-mediated pathologies, which demonstrate a quick and sharp effect of diet on microbiome and subsequently on the onset of the disease [44]. …”
Section: Future Perspectives: Lessons From Hippocratesmentioning
confidence: 59%
“…We observed that mice without acute enteritis that consumed a RS-enriched diet had higher final weights, and a longer colon; the increased body weight and length of the colon is consistent with an increase in the combined mass of the intestinal cells [49]. This may not only translate to enhanced anabolism, but improved mucosal repair, barrier function and enterocyte hyperplasia, contributing to an increase in colon length are well-recognized manifestations of mitigated intestinal inflammation [40]. Although DF intake can reduce feed intake, generally, the total amount of calories required for growth is not affected, and individuals can still maintain a healthy weight [50].…”
Section: Discussionmentioning
confidence: 96%